SOME ASPECTS OF THE CONDUCT CREDIT-MODULAR LEARNING SYSTEMS (Pedagogy of Higher and Secondary Education, 2022)
In article the didactics opportunities of introduction of elements of credit modular training in vocational training the teacher of music are considered; mechanisms of integration the general-didactic and individual-methodical are isolated. Didactics opportunities of a method of testing are analyzed during an estimation of results of performance of educational tasks.
Keywords: credit-modular training; method o f testing; vocational training of the teacher of music; mechanisms of integration; didactic conditions of training; estimating results